2020
DOI: 10.1002/prp2.615
|View full text |Cite
|
Sign up to set email alerts
|

Association between low body weight and cytochrome P‐450 enzyme activity in patients with anorexia nervosa

Abstract: Very little is known to which extent severe underweight could affect cytochrome P‐450 (CYP) enzyme activity. In this study, 24 patients with anorexia nervosa at two occasions ingested single oral doses of five test drugs known to be metabolized by CYP1A2, CYP2C9, CYP2C19, CYP2D6, and CYP3A4, respectively. A mixed model analysis was used to evaluate the effect of changes in body mass index (BMI) on the metabolic activities of these enzymes. The primary end point was the change in drug/metabolite ratio of each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…CYP1A2‐mediated metabolism was not significantly different in patients with obesity and normal to overweight controls, which is in line with previous studies 13,14,45 . Although clearance by CYP1A2 seems to be similar in individuals with different body weights, CYP1A2‐mediated metabolism increased from baseline to week 9 in the diet group.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…CYP1A2‐mediated metabolism was not significantly different in patients with obesity and normal to overweight controls, which is in line with previous studies 13,14,45 . Although clearance by CYP1A2 seems to be similar in individuals with different body weights, CYP1A2‐mediated metabolism increased from baseline to week 9 in the diet group.…”
Section: Discussionsupporting
confidence: 90%
“…This difference diminished over time as CYP2C9‐mediated metabolism decreased significantly in the RYGB group after 3 weeks of LED, before stabilizing, whereas no changes were seen in the diet group. Other studies have not provided evidence of an altered CYP2C9‐mediated metabolism in different body weight ranges or following bariatric surgery 13,42,45 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolic activity of CYP3A4 decreased, while CYP1A2 increased at a higher BMI. CYP2C9, CYP2C19 and CYP2D6 remained unaltered [ 32 ], indicating that CYP3A4 substrates, such as statins or Cyp1A2 substrates like theophylline, might show differences in their efficacy or toxicity, respectively. A further study supported these data showing higher CYP3A4 activity in underweight patients in comparison to normal-weight controls [ 33 ].…”
Section: Dietmentioning
confidence: 99%
“…The isoenzyme CYP3A4 is considered to be primarily involved in the metabolism of PER [ 11 ]. In a recent study on the correlation between body weight and CYP3A activity, [ 12 ] Sandvik et al reported that the enzyme activity of CYP3A4 was higher in patients with anorexia nervosa compared to a control group consisting of individuals with normal weight, and that CYP3A4 activity was negatively correlated with body weight [ 13 ]. Also, CYP3A4 activity was found to decrease with increasing body weight in healthy volunteers [ 14 ].…”
Section: Introductionmentioning
confidence: 99%